Problems of Teaching Reading Skills in English to Nursery School Pupils in South-Western Nigeria - Adegbite, A. B.; Obilade, O. O. (Reading Association of Uganda, 2014)
This study is presented in five sections. Section one introduces the work and presents the research preliminaries such as the problem, aim objectives, justification and hypotheses. Section two highlights the research methodology which includes the use of questionnaire, interview, natural observation and classroom testing. Section three reviews the relevant literature on the topic of the study which includes the role of languages in the education of children, the status of languages in Nigeria and attitudes to them, and the cognitive effects of bilingualism. Section four presents the analyses and discussion of findings of the study, while section five presents the conclusion of the work.